Amidoxime and polydopamine modified loofah sponge adsorbing material and preparation method thereof
By chemically modifying polydopamine and geminoxime groups on the loofah, an efficient geminoxime @ polydopamine modified loofah adsorption material was prepared, which solved the problem of poor adsorption effect of natural loofah on uranyl ions and achieved efficient removal of uranium.
Patent Information
- Application Number
- CN202510014480.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Natural loofah has poor adsorption and removal of uranyl ions in uranium-containing wastewater.
By chemically modifying the loofahs with polydopamine and geminoxime groups, a geminoxime @ polydopamine modified loofah adsorption material was prepared. The material improves the adsorption capacity of uranium through aldehyde synthesis and reaction.
The adsorption effect on uranyl ions is significantly improved, and the uranium in the uranium-containing solution can be effectively removed when the adsorption capacity is maximum, and the optimal adsorption performance is shown under suitable pH conditions.
Smart Images

Figure CN119869465A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment, and in particular to an amidoxime@polydopamine modified loofah adsorption material and a preparation method thereof. Background Art
[0002] Uranium is a radioactive element with strong toxicity and potential carcinogenicity. Uranium ores in nature will seep into the water environment under natural conditions. Under the premise of ensuring safety, nuclear energy is generally considered to be a green energy source, but how to effectively and safely deal with radioactive waste generated by the nuclear industry remains a puzzling challenge. A large amount of radioactive wastewater is generated during the nuclear fuel cycle. In the early stages of uranium mining, ore reprocessing and uranium enrichment, the risk of contamination is considerable. Uranium is one of the main components of nuclear wastewater, and the uranium content can reach tens to hundreds of mg / L. According to the guidelines of the World Health Organization (WHO), the current concentration of U(VI) in environmental wastewater needs to be less than 30μg / L, so the wastewater needs to be comprehensively treated to meet the permissible discharge standards. If improperly treated, the uranium in the wastewater will be released into the environment and accumulated through the food chain. If ingested by the human body, it will eventually cause radiotoxicity and chemical toxicity to biological molecules and even irreversible damage.
[0003] In the treatment of uranium-containing wastewater, the effective removal of U(VI) from low-level radioactive solutions plays an extremely important role in protecting the environment. Several commonly used treatment technologies, including electroflocculation, membrane separation, photocatalysis, ion exchange and bioreduction, have been used to remove U(VI) from low-level radioactive wastewater. Electroflocculation is an advanced coagulation-flocculation method. In this technology, the coagulant is generated by the charge between the cathode and the anode. This process induces the dissolution of metal cations into the water and produces hydroxyl ions at the cathode. Although electroflocculation has a good removal effect on uranium, the electroflocculation equipment consumes more energy. Membrane separation can selectively separate U(VI) from the aqueous phase. It is mainly divided into ultrafiltration (UF), nanofiltration (NF) and reverse osmosis (RO). The advantages include excellent removal effect and the potential for uranium recovery, but the application of membrane separation requires professional knowledge and the recovery rate of the membrane is low. Photocatalysis of uranium is carried out by reducing U(VI) to U(IV), and the obtained U(IV) is then adsorbed on the surface of the photocatalyst. This method is simple to operate and has a high removal rate, but it has disadvantages such as difficulty in recovering the photocatalyst and high dependence on light. Ion exchange is a widely used technology for removing uranium, usually using ion exchange resin as an exchange agent. This method has the advantages of simple equipment and good treatment effect, but the treatment effect of uranium is greatly affected by the exchange agent. The advantages of biological reduction include the simultaneous treatment of organic pollutants and U(VI), the production of uranium in concentrated solid form, and the ability to remove uranium from water where uranium (VI) forms a complex with carbonates. However, the rate and efficiency of biological reduction of U(VI) depend on various biological factors, including pH, temperature, chemical composition of contaminated water, and the composition of microbial communities in the treatment system. Therefore, it is urgent to find a material that can efficiently remove U(VI), is low-cost, biofriendly, and can be used on a large scale.
[0004] Biomass is an environmentally friendly material from forestry and agricultural waste, with low cost, environmental friendliness and excellent biodegradability. Among them, luffa (LC) stands out in the field of adsorption with its unique rigidity and disordered three-dimensional channel structure, hierarchical macropores and honeycomb microchannels. Dry luffa has good mechanical strength and can provide adsorption sites for the adsorption and removal of target pollutants. However, natural untreated luffa has limited adsorption sites and the adsorption effect on uranium is not ideal. Summary of the invention
[0005] The problem in the prior art is that the natural loofah has a poor adsorption and removal effect on uranyl ions in uranium-containing wastewater. In view of the above technical problems, the present invention provides an amidoxime@polydopamine modified loofah adsorption material, and the preparation method thereof comprises the following steps:
[0006] (1) first prepare polydopamine modified loofah, standby;
[0007] (2) then oxidizing the hydroxyl groups on the surface of the polydopamine-modified loofah into aldehyde groups to obtain aldehyde-modified polydopamine-modified loofah;
[0008] (3) The aldehyde group in the aldehyde-modified polydopamine-modified loofah reacts with the hydroxylamine in the hydroxylamine hydrochloride to obtain amidoxime@polydopamine-modified loofah adsorption material.
[0009] Preferably, the method of step (1) comprises the following steps:
[0010] (1) luffa is soaked in water, in aqueous sodium hydroxide solution successively, after immersion is completed, through successively through absolute ethanol washing, washing, drying, obtain pre-treatment luffa;
[0011] (2) Soak the pretreated loofah obtained in step (1) in a mixed solution of anhydrous ethanol and water in a volume ratio of 1:1, add polyoxyethylene polyoxypropylene ether and dopamine, stir evenly, then add 3,3,5,5-tetramethylbenzidine ready-to-use solution, continue to stir evenly, then add concentrated ammonia water, and after the stirring reaction is completed, take out and wash with water and dry to obtain polydopamine modified loofah.
[0012] Preferably, the mass concentration of the sodium hydroxide aqueous solution is 5-10%.
[0013] Preferably, in step (1), the loofah is immersed in water for 12-24 hours and in the sodium hydroxide aqueous solution for 6-12 hours.
[0014] Preferably, the concentration of the concentrated ammonia water is 25-28%.
[0015] Preferably, the usage ratio of polyoxyethylene polyoxypropylene ether to dopamine, 3,3,5,5-tetramethylbenzidine ready-to-use solution, and concentrated ammonia water is 0.5 g: 0.5 g: 1.8 mL: 3 mL.
[0016] Preferably, the method of step (2) comprises the following steps:
[0017] Under light-proof conditions, the polydopamine-modified loofah was added into deionized water, and then sodium periodate and anhydrous calcium chloride were added. After the reaction was completed at 50° C., the loofah was taken out, washed and dried to obtain the aldehyde-modified polydopamine loofah.
[0018] Preferably, the usage ratio of the polydopamine-modified loofah to deionized water, sodium periodate and anhydrous calcium chloride is 0.5 g:50 mL:0.4 g:0.8 g.
[0019] Preferably, the method of step (3) comprises the following steps:
[0020] The aldehyde-modified polydopamine loofah was placed in anhydrous ethanol aqueous solution, hydroxylamine hydrochloride and sodium acetate trihydrate were added, and the mixture was stirred and reacted at 70°C. After the reaction was completed, the mixture was taken out and washed with anhydrous ethanol, deionized water, and dried in sequence to obtain amidoxime@polydopamine modified loofah adsorption material.
[0021] Preferably, the usage ratio of the aldehyde-modified polydopamine-modified loofah to the anhydrous ethanol aqueous solution, hydroxylamine hydrochloride and sodium acetate trihydrate is 0.5 g:100 mL:5 g:10.3 g.
[0022] The present invention has the following beneficial effects:
[0023] (1) The present invention adopts luffa as a carrier because luffa is natural and renewable, environmentally friendly, low cost, high in mechanical strength, easy to recycle, and luffa contains a large amount of hydroxyl functional groups, which can improve its adsorption effect on uranium by chemical modification;
[0024] (2) The present invention uses polydopamine and amidoxime groups to chemically modify natural loofah because polydopamine has good biocompatibility and contains rich functional groups, which can provide additional active sites. The amidoxime groups have good hydrophilicity, which further improves the adsorption capacity of uranium while improving the hydrophilicity of loofah.
[0025] (3) The polydopamine / amidoxime modified loofah material of the present invention is a natural loofah with polydopamine and amidoxime groups added, which has the advantages of low cost, environmental friendliness, good hydrophilicity, and easy recycling, and can better solve the problem of removing uranyl ions in the current radioactive uranium contaminated water;
[0026] (4) In the process of preparing the amidoxime@polydopamine modified loofah adsorption material of the present invention, it is found that when the polydopamine modified loofah base reacts with hydroxylamine hydrochloride for 2 hours, the amidoxime@polydopamine modified loofah adsorption material has the best adsorption effect on uranyl ions in uranium-containing solution;
[0027] (5) The present invention found that when the amidoxime@polydopamine modified loofah adsorption material obtained by the present invention is used to adsorb uranyl ions in a uranium-containing solution, the adsorption effect is best when the pH of the uranium-containing solution is 6. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : is a graph showing the test results of the adsorption capacity of U(VI) by the polydopamine-modified loofah obtained in Examples 1-6 of the present invention in uranium-containing solutions.
[0029] Figure 2: It is a graph showing the adsorption capacity test results of amidoxime@polydopamine modified loofah obtained in Examples 8-12 of the present invention for U(VI) in uranium-containing solutions.
[0030] Figure 3 : is a graph showing the test results of the adsorption capacity of uranyl ions by A-LC / PDA (2) obtained in the present invention in uranium-containing solutions at different pH values.
[0031] Figure 4 : is a graph showing the test results of the adsorption capacity of uranyl ions by A-LC / PDA (2) obtained in the present invention in uranium-containing solutions with different mass concentrations.
[0032] Figure 5 : This is a test result diagram of the comparative results of the adsorption capacities of LC, LC / PDA (4) and A-LC / PDA (2) obtained in the present invention. DETAILED DESCRIPTION
[0033] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0034] The 3,3,5,5-tetramethylbenzidine ready-to-use solution in the following examples of the present invention is a purchased product from Shanghai Adamas Reagent Co., Ltd., model number P9117.
[0035] The loofah used in the following embodiments of the present invention is cut to have dimensions of 10 mm in length, 5 mm in width and 1 mm in height, respectively.
[0036] The uranium-containing solutions used in the following examples of the present invention are all obtained by adding uranyl nitrate to deionized water.
[0037] The pH adjuster used in the following examples of the present invention is a 0.5 M hydrochloric acid aqueous solution or a 0.5 M sodium hydroxide aqueous solution.
[0038] Example 1
[0039] The preparation method of polydopamine modified loofah is as follows:
[0040] (1) at room temperature, the loofah was soaked in water and a 5% sodium hydroxide aqueous solution for 12 h and 6 h respectively, and after the soaking was completed, the loofah was washed (3 times) and dried (80° C., 3 h) to obtain a pretreated loofah;
[0041] (2) 0.5 g of the pretreated loofah obtained in step (1) was soaked in a mixed solution of 100 mL of anhydrous ethanol and water in a volume ratio of 1:1, 0.5 g of polyoxyethylene polyoxypropylene ether (CAS: 9003-11-6) and 0.5 g of dopamine were added, and the mixture was stirred evenly. Then, 1.8 mL of 3,3,5,5-tetramethylbenzidine ready-to-use solution was added, and the mixture was stirred evenly. Then, 3 mL of 25% concentrated ammonia water was added, and the mixture was stirred at 25° C. for 1 h. The mixture was then taken out and washed with anhydrous ethanol 3 times and deionized water 3 times in sequence, and dried at 80° C. for 3 hours to obtain polydopamine-modified loofah, which was recorded as LC / PDA (1).
[0042] Example 2 is the same as Example 1, except that in step (2) of Example 2, the stirring reaction time at room temperature after the addition of concentrated ammonia water is 2 hours, and the product is recorded as LC / PDA (2).
[0043] Example 3 is the same as Example 1, except that in step (2) of Example 3, the stirring reaction time at room temperature after the addition of concentrated ammonia water is 3 hours, and the product is recorded as LC / PDA (3).
[0044] Example 4 is the same as Example 1, except that in step (2) of Example 4, the stirring reaction time at room temperature after the addition of concentrated ammonia water is 4 hours, and the product is recorded as LC / PDA (4).
[0045] Example 5 is the same as Example 1, except that in step (2) of Example 5, the stirring reaction time at room temperature after the addition of concentrated ammonia water is 5 hours, and the product is recorded as LC / PDA (5).
[0046] Example 6 is the same as Example 1, except that in step (2) of Example 6, the stirring reaction time at room temperature after the addition of concentrated ammonia water is 6 hours, and the product is recorded as LC / PDA (6).
[0047] Example 7 is the pretreated loofah obtained in step (1) of Example 1, denoted as LC.
[0048] The adsorption capacity of polydopamine modified loofah obtained in the above Examples 1-6 of the present invention for U(VI) in uranium-containing solution is shown in the attached specification. Figure 1 As shown, the results show that the stirring reaction time at room temperature after the addition of concentrated ammonia water has a significant effect on the adsorption performance of the polydopamine-modified loofah. The adsorption capacity of the polydopamine-modified loofah for U(VI) in the uranium-containing solution increases with the increase of the stirring reaction time at room temperature after the addition of concentrated ammonia water (that is, it increases with the increase of the dopamine polymerization growth time), and tends to be stable after 4 hours.
[0049] The adsorption capacity test method is as follows:
[0050] (1) adding uranyl nitrate to deionized water to obtain a uranium-containing solution with a mass concentration of 20 mg / L;
[0051] (2) 0.02 g of the adsorbent material was added to 100 mL of the uranium-containing solution obtained in step (1), and adsorption equilibrium was reached using a stirrer at 25° C. After the adsorption was completed, the concentration of residual U(VI) in the solution was detected, and the adsorption capacity of the adsorbent material was calculated.
[0052] Example 8
[0053] The preparation method of amidoxime@polydopamine modified loofah adsorption material is as follows:
[0054] (1) Under light-proof conditions, 0.5 g of the polydopamine-modified loofah obtained in Example 4 was weighed and added to 50 mL of deionized water, and then 0.4 g of sodium periodate and 0.8 g of anhydrous calcium chloride were added, and the mixture was stirred at 50° C. and 150 r / min for 4 h. After the reaction was completed, the loofah was taken out, rinsed with deionized water 3 times, and then placed in an oven and dried at 80° C. for 3 h to obtain a aldehyde-modified polydopamine-modified loofah;
[0055] (2) Weigh 0.5 g of formaldehyde-modified polydopamine loofah and add it to a mixed solution of 100 mL of anhydrous ethanol and deionized water in a volume ratio of 1:1, then add 5 g of hydroxylamine hydrochloride and 10.3 g of sodium acetate trihydrate, and stir at 70 ° C and 150 r / min for 1 h. After the reaction is completed, take out the loofah, wash it with anhydrous ethanol 3 times, rinse it with deionized water 3 times, and then place it in an oven at 80 ° C for 3 h to obtain amidoxime@polydopamine modified loofah adsorption material, which is recorded as A-LC / PDA (1).
[0056] Example 9 is the same as Example 8, except that the stirring reaction time at 70° C. in step (2) of Example 9 is 2 h, and the product is recorded as A-LC / PDA (2).
[0057] Example 10 is the same as Example 8, except that the stirring reaction time at 70° C. in step (2) of Example 10 is 3 h, and the product is recorded as A-LC / PDA (3).
[0058] Example 11 is the same as Example 8, except that the stirring reaction time at 70° C. in step (2) of Example 11 is 4 h, and the product is recorded as A-LC / PDA (4).
[0059] Example 12 is the same as Example 8, except that the stirring reaction time at 70° C. in step (2) of Example 12 is 5 h, and the product is recorded as A-LC / PDA (5).
[0060] The adsorption capacity of amidoxime@polydopamine modified loofah obtained in the above Examples 8-12 of the present invention for U(VI) in uranium-containing solution is shown in the attached manual. Figure 2 As shown, the results show that the stirring reaction time at 70°C in step (2) has a significant effect on the adsorption capacity of the amidoxime@polydopamine modified loofah. When the stirring reaction time at 70°C is 2h, the adsorption capacity of the amidoxime@polydopamine modified loofah obtained in Example 9 is the largest.
[0061] The adsorption capacity test method is as follows:
[0062] (1) adding uranyl nitrate to deionized water to obtain a uranium-containing solution with a mass concentration of 20 mg / L;
[0063] (2) 0.02 g of the adsorbent material was added to 100 mL of the uranium-containing solution obtained in step (1), and adsorption equilibrium was reached using a stirrer at 25° C. After the adsorption was completed, the concentration of residual U(VI) in the solution was detected, and the adsorption capacity of the adsorbent material was calculated.
[0064] Embodiment 13
[0065] A method for removing uranyl ions from a uranium-containing solution by using amidoxime@polydopamine modified loofah is as follows:
[0066] (1) At 25°C, adjust the pH of the uranium-containing solution to 3, 4, 5, 6, 7, 8, or 9 for later use;
[0067] (2) 100 mL of uranyl solutions with pH values of 3, 4, 5, 6, 7, 8, and 9 were taken respectively, and 0.02 g of A-LC / PDA (2) obtained in Example 9 was added respectively, and the mixture was stirred at a rate of 150 r / min until adsorption equilibrium (i.e., the concentration of uranyl ions in the uranyl solutions was constant). The adsorption capacity of A-LC / PDA (2) for uranyl ions in uranyl solutions at different pH values was shown in the attached manual. Figure 3 As shown. The test results show that when the pH value of the uranium-containing solution is 3.0-4.0, the adsorption capacity of A-LC / PDA(2) for U(VI) is low, when the pH value of the uranium-containing solution is 5.0-7.0, the adsorption capacity of A-LC / PDA(2) for U(VI) is greatly improved, and when the pH value of the uranium-containing solution is 8.0-9.0, the adsorption capacity of A-LC / PDA(2) for U(VI) decreases significantly. Among them, when the pH of the uranium-containing solution is 6.0, the adsorption capacity of A-LC / PDA(2) for U(VI) is the highest. Therefore, the optimal adsorption pH condition of amidoxime@polydopamine modified loofah obtained by the present invention for U(VI) is 6.0.
[0068] Embodiment 14
[0069] Uranium-containing solutions with concentrations of 20, 30, 40, 50, and 60 mg / L were prepared, and the pH was adjusted to 6. 100 mL of uranium-containing solutions of different mass concentrations were taken, and 0.02 g of A-LC / PDA (2) obtained in Example 9 was added, respectively. The mixture was stirred at a rate of 150 r / min at 25° C., 35° C., and 45° C. until adsorption equilibrium was reached. The adsorption capacity of A-LC / PDA (2) for uranyl ions in uranium-containing solutions of different mass concentrations at different temperatures is shown in the attached manual. Figure 4 The test shows that, at the same concentration, the adsorption capacity of A-LC / PDA(2) for U(VI) increases with the increase of temperature. At the same temperature, the adsorption capacity of A-LC / PDA(2) for U(VI) increases with the increase of U(VI) concentration in the aqueous solution. Therefore, the adsorption capacity of amidoxime@polydopamine modified loofah obtained by the present invention for U(VI) is proportional to the ambient temperature and U(VI) concentration.
[0070] Embodiment 15
[0071] Take three portions of 100 mL of uranium solution with a mass concentration of 20 mg / L (25°C), adjust the pH to 6, and add 0.02 g of unmodified loofah LC, LC / PDA (4), and A-LC / PDA (2) respectively. Stir at 25°C at a rate of 150 r / min until adsorption equilibrium. The adsorption capacity comparison results of LC, LC / PDA (4), and A-LC / PDA (2) are shown in the attached manual. Figure 5 The results show that the adsorption capacity of LC for U(VI) is very low, which is 16.789 mg / g. The adsorption capacities of LC / PDA(4) and A-LC / PDA(2) are 48.902 mg / g and 65.569 mg / g, respectively. The adsorption capacity of A-LC / PDA(2) is increased by 290.55% compared with LC and 34.08% compared with LC / PDA(4).
[0072] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A amidoxime@polydopamine modified loofah adsorption material, characterized in that: The preparation method comprises the following steps: (1) first prepare polydopamine modified loofah, standby; (2) then oxidizing the hydroxyl groups on the surface of the polydopamine-modified loofah into aldehyde groups to obtain aldehyde-modified polydopamine-modified loofah; (3) The aldehyde group in the aldehyde-modified polydopamine-modified loofah reacts with the hydroxylamine in the hydroxylamine hydrochloride to obtain amidoxime@polydopamine-modified loofah adsorption material.
2. The amidoxime@polydopamine modified loofah adsorption material according to claim 1, characterized in that: The method of step (1) comprises the following steps: (1) the luffa is soaked in water and sodium hydroxide aqueous solution successively, and after the soaking is completed, the luffa is washed with absolute ethanol, washed with water, and dried successively to obtain the pre-treatment luffa; (2) Soak the pretreated loofah obtained in step (1) in a mixed solution of anhydrous ethanol and water in a volume ratio of 1:1, add polyoxyethylene polyoxypropylene ether and dopamine, stir evenly, then add 3,3,5,5-tetramethylbenzidine ready-to-use solution, continue to stir evenly, then add concentrated ammonia water, and after the stirring reaction is completed, take out and wash with water and dry to obtain polydopamine modified loofah.
3. A amidoxime@polydopamine modified loofah adsorption material according to claim 2, characterized in that, In step (1), the loofah is immersed in water for 12-24 hours, and immersed in sodium hydroxide aqueous solution for 6-12 hours.
4. The amidoxime@polydopamine modified loofah adsorption material according to claim 2, characterized in that: The concentration of the concentrated ammonia water is 25-28%.
5. The amidoxime@polydopamine modified loofah adsorption material according to claim 2, characterized in that: The dosage ratio of polyoxyethylene polyoxypropylene ether to dopamine, 3,3,5,5-tetramethylbenzidine ready-to-use solution, and concentrated ammonia water is 0.5g:0.5g:1.8mL:3mL.
6. The amidoxime@polydopamine modified loofah adsorption material according to claim 1, characterized in that: The method of step (2) comprises the following steps: Under light-proof conditions, the polydopamine-modified loofah was added into deionized water, and then sodium periodate and anhydrous calcium chloride were added. After the reaction was completed at 50° C., the loofah was taken out, washed and dried to obtain the aldehyde-modified polydopamine loofah.
7. The amidoxime@polydopamine modified loofah adsorption material according to claim 6, characterized in that: The usage ratio of polydopamine modified loofah to deionized water, sodium periodate and anhydrous calcium chloride is 0.5g:50mL:0.4g:0.8g.
8. The amidoxime@polydopamine modified loofah adsorption material according to claim 1, characterized in that: The method of step (3) comprises the following steps: The aldehyde-modified polydopamine loofah was placed in anhydrous ethanol aqueous solution, hydroxylamine hydrochloride and sodium acetate trihydrate were added, and the mixture was stirred and reacted at 70°C. After the reaction was completed, the mixture was taken out and washed with anhydrous ethanol, deionized water, and dried in sequence to obtain amidoxime@polydopamine modified loofah adsorption material.
9. The amidoxime@polydopamine modified loofah adsorption material according to claim 8, characterized in that: The dosage ratio of the aldehyde-modified polydopamine-modified loofah to the anhydrous ethanol aqueous solution, hydroxylamine hydrochloride and sodium acetate trihydrate is 0.5 g:100 mL:5 g:10.3 g.
10. A method for removing uranyl ions from uranium-containing wastewater, characterized in that: The pH of the uranium-containing wastewater is adjusted to 6 using hydrochloric acid solution or sodium hydroxide solution as a pH regulator, and the amidoxime@polydopamine modified loofah adsorption material obtained according to any one of claims 1 to 9 is added to the uranium-containing wastewater, and adsorbed by stirring at different temperatures until equilibrium is reached.
Citation Information
Patent Citations
Modified loofah sponge absorbent for uranium extraction from seawater and preparation method for loofah sponge absorbent
CN105312041A
Amidoximation adsorption material as well as preparation method and application thereof
CN112808244A
Corn straw bio-adsorbent for treating uranium-containing wastewater and preparation method of corn straw bio-adsorbent
CN118416869A
Targeted delivery system of multivalent conjugate based on polydopamine nanosphere coupling aptamer as well as drug loading method and application of targeted delivery system
CN118949067A